Integrated Behavioral Perceptual Evaluation for Comparative E-Commerce Web Usability: Evidence from Shopee and Tokopedia - Mifta Fauzia Rahma; Chanifah Indah Ratnasari (Jurnal Pendidikan Informatika (EDUMATIC), 2026)
The growth of e-commerce has intensified competition among digital platforms, making usability a crucial factor in user engagement and convenience. However, many usability studies rely on single-method evaluation approaches, rarely conduct cross-platform comparisons, and seldom examine the relationship between perceived usability and behavioral interaction efficiency. This study compared the web usability of Shopee and Tokopedia by combining subjective usability assessment with eye-tracking analysis. Thirty-nine participants completed search, filter, and cart tasks on both platforms while gaze data were recorded and then completed the USE Questionnaire. The data were analyzed using non-parametric tests and AOI-based eye-tracking metrics. The results showed that both platforms achieved comparable perceived usability and received a “Good” classification. However, eye-tracking findings revealed task-dependent differences in visual attention, particularly during search activities. These findings demonstrate that perceived usability equivalence does not necessarily indicate behavioral interaction efficiency. This study contributes methodologically by proposing an integrated evaluation framework that combines biometric and psychometric measures, and theoretically by providing empirical evidence of the divergence between subjective perceptions and objective behavioral efficiency, with implications for improving visual hierarchy and navigation in e-commerce interfaces.